New indications for dabigatran: A suggestion from a drug use evaluation study - Farzaneh Ashrafi; Najmeh Rezaie; Sarah Mousavi (Wolters Kluwer Medknow Publications, 2017)
Objective: Dabigatran etexilate is a novel oral anticoagulant with several advantages over warfarin such as no need for routine monitoring and fewer drug interactions. This drug was added to our hospital's formulary in 2012. The objective of this study was to assess the rational drug use of dabigatran at a large teaching hospital. Methods: A prospective cross-sectional study was performed from November to June 2015 at Alzahra teaching hospital, Isfahan, Iran. All patients who received at least one dose of dabigatran were eligible for inclusion. Data were collected on patient demographics, indication, dosing regimen, adverse events, concurrent anticoagulant therapy, and laboratory data (including renal function). Findings: A total of sixty patients were included in our study. The majority of patients (n = 40, 66.7%) was prescribed dabigatran for deep vein thrombosis prophylaxis. Only one patient received dabigatran with appropriate indication, dose, and duration. Thirty-six (60%) of our patients had thrombocytopenia at the time of dabigatran initiation. We also detected that ten patients (16.7%) received this drug for heparin-induced thrombocytopenia (HIT). In 32 patients, platelet levels increased after dabigatran initiation. Only seven patients received the appropriate dose of dabigatran (regarding both indication and renal function). Conclusion: Unlabeled use and incorrect dosing of dabigatran in this study emphasize the need to develop a hospital protocol for dabigatran use within our facility. We suggest proper education of clinicians about novel drugs, pharmacist interventions, and further studies about the safety and efficacy of dabigatran for the new indication (such as HIT).